Case Report: Unable to Jump Like a Kangaroo Due to Myositis Ossificans Circumscripta - Huenerfauth, Enrice I.; Molnár, Viktor; Rosati, Marco; Ciurkiewicz, Malgorzata; Söbbeler, Franz J.; Harms, Oliver; Hildebrandt, Robert; Baumgärtner, Wolfgang; Tipold, Andrea; Volk, Holger A.; Nessler, Jasmin (Frontiers in Veterinary Science, 2022)
A male 10-year-old captive red kangaroo (Macropus rufus) was presented with a chronic progressive pelvic limb lameness and reluctance to jump. The general examination revealed a palpable induration of lumbar epaxial muscles. Magnetic resonance imaging performed under general anesthesia revealed bilateral almost symmetric, well-circumscribed mass lesions in superficial erector spinae muscles. The lesions had an irregular to multilobulated appearance with hyper-, hypo-, and isointense areas in T2- and T1-weighted (w) sequences without contrast enhancement. On computed tomography, a peripheral rim of mineralization was apparent. Histopathological analysis of a muscle biopsy showed osseous trabeculae with rare clusters of chondrocytes indicating metaplasia of muscle tissue to bone. No indications of inflammation or malignancy were visible. The clinical, histopathological, and imaging workup of this case was consistent with myositis ossificans circumscripta. This disorder is particularly well-known amongst human professional athletes, like basketball players, where excessive, chronic-repetitive force or blunt trauma causes microtrauma to the musculature. Metaplasia of muscle tissue due to abnormal regeneration processes cause heterotopic ossification. The kangaroo´s clinical signs improved with cyto-reductive surgery, cage rest, weight reduction, and meloxicam without further relapse.